Assessment of marine debris in beaches or seawaters around the China Seas and coastal provinces. (February 2016) - Zhou, Changchun; Liu, Xu; Wang, Zhengwen; Yang, Tiantian; Shi, Linna; Wang, Linlin; You, Suwen; Li, Min; Zhang, Cuicui
Highlights: The study on the abundance, composition and sources of marine debris was done in beaches and seawaters around the China Seas and coastal provinces. The results showed mean number and weight densities of beached marine debris (BMD), floating marine debris (FMD) and seafloor marine debris (SMD) with plastics, Styrofoam and wood dominating. Furthermore, the primary sources of BMD and FMD were coastal/recreational activities and other disposals, while the main source of SMD remained unknown. This study provides the quantitative evidence for future comparisons with other countries and contributes to the understanding, control and mitigation of such contaminant in the context of China's current condition of high-speed socio-economic development and severe environmental deterioration. Abstract: Compared with United States of America (USA), Brazil, Chile, Australia, limited attention has been paid to marine debris research in China and few studies have attempted to quantify the abundance and mass of marine debris. In this study, firstly the general status and sources of marine debris in China were assessed in the time period between 2007 and 2014, and secondly marine debris situation was evaluated in three China Sea Areas (the North China Sea, the East China Sea and the South China Sea) from 2009 to 2013, and finally marine debris conditions and sources were analyzed in beaches or seawaters around some coastal provinces of China during 2007–2013. Based on above analysis, the primary conclusions were as follows: (1) The mean number and weight densities of beached marine debris (BMD) and submerged marine debris (SMD) were 4.30, 0.13 items/100 m 2 and 133.80, 22.60 g/100 m 2 in China from 2007 to 2014, respectively. The average number density of the large size FMD (LOSFMD) was 0.0024 items/100 m 2 and that of the small and medium size FMD (SMSFMD) was 0.30 items/100 m 2, and the mean weight density of the SMSFMD was 1.40 g/100 m 2 from 2008 to 2014. The SMD and FMD densities were at the low level and the BMD density was at the high level in China. (2) The marine debris primarily was comprised of plastic, Styrofoam, wood, glass, rubber, fabric/fiber and metal, which included almost all major categories of marine debris. (3) Sources of BMD and FMD were as follows: the first source was coastal/recreational activities, followed by other disposal sources, navigation/fishing activities and the activities related smoking, and the least source being those associated with medical/sanitary activities, while the source of SMD remained unknown. (4) The mean number and weight densities of BMD were the biggest in the North China Sea, while those of FMD and SMD were the highest in the northern South China Sea. The results of this study were beneficial to the establishment of management measures for dealing with ecological and environmental problems that were generated by the high speed socio-economic development in China.